2005
DOI: 10.1038/sj.thj.6200574
|View full text |Cite
|
Sign up to set email alerts
|

The effect of iron deficiency anemia on the function of the immune system

Abstract: We aimed to study the effect of iron deficiency anemia (IDA) on immunity. In 32 children with IDA and 29 normal children, the percentage of T-lymphocyte subgroups, the level of serum interleukin-6 (IL-6); and the phagocytic activity, the oxidative burst activity of neutrophils and monocytes and the levels of immunoglobulins were compared. There was no difference in the distribution of T-lymphocyte subgroups. The mean IL-6 levels was 5.6+/-3.9 pg/ml in children with IDA and 10.3+/-5.3 pg/ml in the control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
156
7
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(185 citation statements)
references
References 27 publications
14
156
7
8
Order By: Relevance
“…In contrast with our fi ndings, Ekiz et al [5] reported that there was no change in the T-lymphocyte numbers and distribution of subgroups in cases with IDA. The reported T-cell dysfunction may be the result of functional defects of T-cells rather than quantitative defects.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast with our fi ndings, Ekiz et al [5] reported that there was no change in the T-lymphocyte numbers and distribution of subgroups in cases with IDA. The reported T-cell dysfunction may be the result of functional defects of T-cells rather than quantitative defects.…”
Section: Discussioncontrasting
confidence: 99%
“…While the prevalance of iron defi ciency varies across the world, It is well known that children and women in the reproductive age group are especially vulnerable to iron defi ciency [1]. Both experimental and some clinical studies have emphasized the importance of iron in the integrity of the immune system especially in the innate immunity and the cellular component system of active immunity [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selenium supplementation prevents cell damage and plays an important role in the development, fertility, and immune functions of humans and other vertebrates, including fish (Hoffmann and Berry, 2008;Schrauzer and Surai, 2009). However, its deficiency causes many metabolic disorders and diseases such as calf pneumonia, white muscle disease in calves and beef cows, exudative diathesis, and infertility in fish and other vertebrates; thus, a lack of selenium exerts a negative influence on the immune function (Muller et al, 2002;Ekiz et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Iron deficiency has been associated with defects in both adaptive and innate immunity (Cunningham-Rundles et al 2005). Furthermore, iron deficiency anaemia in children is associated with reductions in both phagocytic activity and immunoglobulin levels (Ekiz et al 2005).…”
mentioning
confidence: 99%